Ramón García de Haro, La vida Cristiana. Ediciones Univ. de Navarra, Pamplona, 1992, 849 pp. - Derisi, Octavio Nicolás (1994)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina